What triggers impulse purchase in Facebook commerce? - Leong, Lai Ying; Jaafar, Noor Ismawati; Ainin, Sulaiman (Inderscience, 2018)
Facebook commerce or f-commerce has become a new trend in mobile commerce (m-commerce) due to the advancements in mobile communications and social media technologies. Despite a huge business potential in f-commerce, impulse purchase in f-commerce is still not wellunderstood. Unlike previous f-commerce studies which had focused on apparel; e-service quality; organic rice; and membership continuance intention, the current study investigated utilitarian-, hedonic-, and trust-motivations' effects on participation that influences urge to purchase and ultimately impulse purchase. The effects of the personality trait of urgency towards urge to purchase and impulse purchase were also examined. A sample of f-commerce users was selected and their responses were analysed using PLS-SEM. The model can explain 52.8%, 47.4%, 41.1% and 33.3% variance in impulse purchase, participation, urge to purchase and trust. These findings will be beneficial to the mobile commerce retailers, marketers and other f-commerce stakeholders in formulating their marketing strategies and policies.